Influence of Phosphate Starvation on Cultures of Pseudomonas aeruginosa - Hou, Cynthia I. (1966)
Hou, Cynthia I. (University of British Columbia, Vancouver, B.C., Canada), Audrey F. Gronlund, and J. J. R. Campbell. Influence of phosphate starvation on cultures of Pseudomonas aeruginosa. J. Bacteriol. 92:851–855. 1966.—The changes occurring in Pseudomonas aeruginosa during phosphate starvation in a phosphate-deficient medium were assessed by measuring alterations in optical density, viable-cell count, chemical composition, and ribosome patterns. After a 24-hr period of starvation, optical density, protein, and deoxyribonucleic acid per milliliter of culture increased, whereas ribonucleic acid decreased. Extensive ribosomal degradation was apparent from sucrose density gradient centrifugation patterns. The induction of an alkaline phosphomonoesterase during phosphate starvation was observed. A linear response of phosphate-starved cells to low levels of phosphate supplied exogenously was evident from optical-density measurements, and a threshold requirement for phosphate analogous to the “energy of maintenance” was not detected.